PENGARUH KUALITAS LAYANAN MOBILE BANKING TERHADAP KEPUASAN NASABAH BANK ACEH SYARIAH DI KECAMATAN KUTA ALAM - Diva, Intan; Ashal, Farid Fathony; Ridha, Ismail Rasyid (Journal of Sharia Economics, 2022)
Mobile banking services answer all the needs of customers in digital transactions, but also have problems with the lack of service features offered, so that they are not in line with customer expectations. The purpose of this study is to reveal the effect of mobile banking service quality on customer satisfaction at Bank Aceh Syariah in Kuta Alam District. This study uses a quantitative approach. The results showed that the quality of mobile banking services had a positive and significant effect on customer satisfaction, based on the coefficient of determination (R2) test, it was obtained at 0.400 which means that the variable (X) of service quality can partially explain the relationship with the customer satisfaction variable (Y) by 40% and the remaining 60%. , explained by other variables not explained in this study. Keywords: Service Quality, Customer Satisfaction, Mobile Banking